Dependência de polinização e polinizadores do Mirtilo ‘Rabbiteye’ (Vaccinium virgatum A.; Ericaceae) - Jesus, Murillo Fernando de Souza (2022)
‘Rabbiteye’ blueberry group (Vaccinium virgatum A.) is native from the United States and has originated many cultivars of the crop, including ‘Bluebelle’, ‘Bluegem’ and ‘Delite’. Blueberry pollination dependency is variable between plant varieties and cultivars and in its worldwide growth, which tends to tamper the pollinator management available at the growth sites. The objective of this dissertation is to survey the entomophilic pollinator influence and the diversity of floral visitors available to blueberry crop growth in southern Brazil, with emphasis on the ‘Bluebelle’, ‘Bluegem’ and ‘Delite’ cultivars. The presented work was organized in two chapters, with the first one linked to blueberry pollinator influence on the fruit of three cultivars and the second one linked to blueberry floral visitators and its pollen collection by stingless bees, both taken place in the same study area in the municipality of Guaíba, Rio Grande do Sul, Brazil. To survey the pollinator influence and the effect of buzz-pollination on the plant, plant inflorescences were selected and observed in four treatments based on pollination type: self-pollination; self-pollination with buzzing; open pollination and open pollination with buzzing. Initially, the fruit were quantified for fructification rates and collected after proper ripening for a sampling of size, weight, and seed number. ‘Bluegem’ cultivar presented the higher pollinator dependency, showing fructification rates below 8% for both self-pollination treatments. Similarly, ‘Bluebelle’ and ‘Delite’ cultivars presented low fructification rates for “self-pollination”, but not for “self-pollination with buzzing”, which presents rates of 47,5% and 62,3% respectively for each of these two cultivars. The buzzing effect, however, did not rise up significantly the fructification in either cultivar in open pollination treatments, compared to self-pollination treatments when the buzzing increased fructification rates. In the second chapter the wild floral visitor density at three different times of day was surveyed, as well the pollen collection of stingless bees species (Melipona quadrifasciata and Melipona torrida), which were introduced in the study area through managed hives along the studied plants. For the wild visitor's survey, their visitations in the plants were quantified through transect walks in crop growth lines of the orchard, along with the quantification of open flowers for the calculation of visitation density. To survey the stingless bees' collected pollen proportion, four hives from each species were placed in field, with the pollen sampled from sampled foragers corbiculae for identification. There was a positive correlation between the number of open flowers with the number of visitations, however, there weren’t differences between the times of the day. Individuals of Hymenoptera, Diptera, Lepidoptera, Hemiptera, and Coleoptera, besides birds from Trochillidae family, were observed in the flowers. Dominance was taken by Apis mellifera (73,7%) and Trigona spinipes (17,4%) bees, with the remaining groups presented in 8,8% of total visitations. In the managed stingless bees, M. quadrifasciata and M. torrida, foragers were carrying blueberry pollen, however in low proportion (0,25% of total grains).